2018
DOI: 10.1534/genetics.117.300552
|View full text |Cite
|
Sign up to set email alerts
|

The Hidden Genomic and Transcriptomic Plasticity of Giant Marker Chromosomes in Cancer

Abstract: Genome amplification in the form of rings or giant rod-shaped marker chromosomes (RGMs) is a common genetic alteration in soft tissue tumors. The mitotic stability of these structures is often rescued by perfectly functioning analphoid neocentromeres, which therefore significantly contribute to cancer progression. Here, we disentangled the genomic architecture of many neocentromeres stabilizing marker chromosomes in well-differentiated liposarcoma and lung sarcomatoid carcinoma samples. In cells carrying heavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…A recent work by Hänsel-Hertsch and colleagues 22 supported by previous literature 50, [68][69][70] showed that cancer-related copy number variants (CNVs), i.e., amplifications, as well as single nucleotide variants, are enriched in breast cancer-specific G4s. To test whether WDLPS-specific G4s were associated with CNVs and also pan-cancer somatic variants (SVs), we calculated the overlap between 93T449 cell-specific CNVs or SVs 37 , and G4 peaks found in 93T449 or HaCaT cells. We found that 73% of 93T449 CNVs (299 out of 411 detected CNVs) overlapped with folded G4s peaks, and 47% of all CNVs (193 out of 411) were in genomic regions that harbor 93T449 cell line-specific G4s (i.e., G4s that are not folded in the HaCaT cell line).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent work by Hänsel-Hertsch and colleagues 22 supported by previous literature 50, [68][69][70] showed that cancer-related copy number variants (CNVs), i.e., amplifications, as well as single nucleotide variants, are enriched in breast cancer-specific G4s. To test whether WDLPS-specific G4s were associated with CNVs and also pan-cancer somatic variants (SVs), we calculated the overlap between 93T449 cell-specific CNVs or SVs 37 , and G4 peaks found in 93T449 or HaCaT cells. We found that 73% of 93T449 CNVs (299 out of 411 detected CNVs) overlapped with folded G4s peaks, and 47% of all CNVs (193 out of 411) were in genomic regions that harbor 93T449 cell line-specific G4s (i.e., G4s that are not folded in the HaCaT cell line).…”
Section: Resultsmentioning
confidence: 99%
“…The R package "ChIPpeakAnno" 34,94 was employed to calculate overlapping of 93T449 CNVs and SVs regions with G4-ChIP-seq peaks. CNVs data obtained by BICseq and SVs obtained by WGS (Crest) were retrieved from Macchia et al 37 . Genomic regions coordinates were converted from GRCh37/hg19 to GRCh38/hg38 by mean of UCSC Lift Genome Annotations tool (https://genome.ucsc.edu/cgi-bin/hgLiftOver).…”
Section: Reporting Summary Further Information On Research Design Is Available In the Naturementioning
confidence: 99%
See 1 more Smart Citation
“…MDM2 amplification in WDLPS is associated to the formation of giant ring marker chromosomes containing multiple copies of the gene. Chimeric and fusion transcripts arising from such unstable regions are hypothesized to push the genomic amplification process during tumour progression ( 70 ). The deficiency of one or more MDM2 G4 binding/unwinding proteins may cause replicative stress that worsens or is at the root of the pathological genome amplification, as recently proposed for ATRX-deficient malignant glioma ( 71 ).…”
Section: Discussionmentioning
confidence: 99%
“…In ring-chromosomes, the ends of the DNA sequence are fused together to form a ring shape [ 12 ]. Neochromosomes contain centromere and telomere sequences, with a typical sequence length of 30–600 Mb [ 7 , 8 ]. Neochromosomes have been shown to contain high copy numbers of oncogenes and can be created through chromothripsis [ 9 ].…”
Section: Introductionmentioning
confidence: 99%